Kara Fazlı’nin hayatı, eserleri, edebi kişiliği ve divanı: (incleme-tenkitli Metin) - Özkat, Mustafa (My University, 2005)
Klâsik Türk edebiyatında Gül ü Bülbül adlı mesnevîsiyle tanınmış olan Fazlî, Kânûnî Sultan Süleyman devri (1520-1566) şairlerindendir. Adı Mehmet Ali olan ve İstanbul'da doğan şair, bir saracın oğlu olması nedeniyle Saraç-zâde, esmer tenli oluşu nedeniyle de Kara Fazlî lakabıyla anılmıştır Fazlî'nin şairliği ile birlikte memuriyet hayatı, Kânûnî'nin şehzâdeleri Mehmet, Mustafa ve Selim'in sünnet edildiği 27 Haziran 1530 tarihinden sonra, adı geçen üç şehzâdenin dîvân kâtipliği ile geçmiş ve reisü'l-küttâblığa yükseldiği Şehzâde Selim'in Kütahya valiliği sırasında ölümüyle son bulmuştur (Mayıs 1564). Zâtî'nin öğrencileri arasında yer alan Fazlî, Üsküplü Riyazî'den Farsça tahsil etmiş, Şeyh Zarîfî Hasan Efendi'ye bağlanarak Halvetî tarikatına girmiştir. Tasavvufa eğilimine rağmen mutasavvıf bir şair değildir. Tezkirelerin belirttiğine göre hamse sahibi olan şairin Dîvân ve Rubâ'iyyât'ından başka Hümây u Hümâyûn, Lüccetü'l-Esrâr ve Gül ü Bülbül adlı mesnevîleri ile manzum-mensur karışık olarak yazdığı Nahlistân, Tehniyet-nâme ve Duâ-nâme adlı eserleri vardır. Münşe'at'ı da bulunan şairin nesri de nazmı kadar güçlüdür. Bilgili, faziletli, güzel söz söyleme sanatına vakıf, şiire hakim ve derviş mizaçlı bir kişiliğe sahiptir. Kelime oyunlarından uzak ve sade bir söyleyişe sahip şiirlerinde kelimenin ruhunu bulmuş, bir kuyumcu titizliği ile şiire duygu ve zekâ katmasını bilmiştir. Şiir mecmualarını tarayarak derlediğimiz Dîvân'ında 34 kasîde, 38 musammat, 8 tarih, 153 gazel, 20 kıt'a ve 2 müfret yer almaktadır. Dîvân'ında yer alan şiirlerinde Türkçe kelimelere ağırlık vermiş, deyim ve atasözlerinden de yararlanarak konuşma diline dayanan sağlam bir Türkçe oluşturmaya çalışmıştır. Bu özelliğinde Türkî-i Basit akımı ile birlikte Zâtî'nin etkisi büyük rol oynamıştır. Famous for his poem Gül ü Bülbül (Rose and Nightingale) in Classic Turkish Literature, Fazli has been a distinguished poet during the reign of Suleyman the Magnificent (1520-1566). His real name was Mehmet Ali. He was born in İstanbul as the son of a saddler so he was called Saraç-zade (saddler's son), and because he was dark skinned, he was also known as Kara Fazli (Fazli the Black). Not only was he an eminent poet of his age but also he emerged as the secretary in supreme council (divan katibi) to three princes of Suleyman the Magnificent- Mehmet, Mustafa and Selim- in 27 June, 1530 when they were circumcised. The time when Prince Selim turned out to be the governor in Kütahya, he was promoted to the reisü'l-küttab and in May 1564, he passed away. A student of Zati's, Fazli learnt Persian from Riyazi of Skopje, and he became a member of Halveti sect under Seyh Zarifi Hasan Efendi. Although he was highly interested in mystic Islam philosophy, he was not a theosophic poet. Fazli is reported, in several documents, to have given literary works such as Divan (a collection of poems) and Ruba'iyyat as well as Hümay u Hümayun, Leccetü'l Esrar and Gül ü Bülbül (Rose and Nightingale). Also among these were Nahlistan, Tehniyetname and Dua-name (book of prayers)- his three literary works written in prose and verse. Having written also Münse'at, Fazli has been a distinguished writer as well as a poet. A learned man of wisdom, very skillful in rhetoric, and very much noted in poetry, Fazli had a dervish-like temparement. He has discovered the spirit of words in his poems of plain Turkish, and he has meticulously put into them all his senses and wise. His collection of lyric poems, which consists of 34 kaside's(panegyrics), 38 musammat, 8 tarih (chronicles), 153 gazel's (ode, ghazel), 20 kıt'a (stanzas) and 2 müfret, has been brought together here in this thesis by the study of the magazines of poetry. In his collection, he has paid special attention to the use of Turkish words and by making the most of idioms and proverbs and under the influence of the School of Türki-i Basit and Zati, he has highly relied on everyday spoken Turkis
Keywords: Divan Şiiri; Edebiyat; Kara Fazlı’; Osmanlıca edebiyat; Osmanlıca şiir (Divan şiiri); Türk Edebiyatı